2004
DOI: 10.1016/j.rmed.2003.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Self-administration and standardisation of the chronic respiratory questionnaire: a randomised trial in three German-speaking countries

Abstract: The chronic respiratory questionnaire (CRQ) has demonstrated excellent measurement properties in patients with chronic obstructive pulmonary disease (COPD), but in its original form it is limited by the requirement for interviewer-administration and the individualised dyspnoea questions. The objective of this randomised trial was to examine the evaluative properties of the interviewer and self-administered German CRQ as well as of a standardised CRQ dyspnoea domain. In a multinational trial we randomly allocat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 23 publications
2
37
0
1
Order By: Relevance
“…sample (Table 1) presented relatively preserved exercise capacity in relation to that of patients participating in previous studies. (11,13,14) When comparing the scores of each CRQ domain obtained for the Brazilian patients with those obtained for patients from other countries in which the CRQ was validated, (13,14) we observed that the scores found for the fatigue, emotional function and mastery domains in the present study (4.5 ± 1.2; 4.8 ± 1.0; and 5.1 ± 1.3, respectively) were similar to those found for the Spanish-language version (4.47 ± 1.20; 4.80 ± 1.26; and 5.0 ± 1.5, respectively) and those found for the German-language version, with the exception of the mastery domain (4.2 ± 1.2, 4.4 ± 1.0 and 4.4 ± 1.2, respectively). However, for the dyspnea domain, the score obtained for the Brazilian population was considerably higher (4.6 ± 1.3) than that obtained for the Spanish population (3.15 ± 1.00) and for the Germanspeaking population (3.17 ± 0.66), indicating a better quality of life for this domain.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…sample (Table 1) presented relatively preserved exercise capacity in relation to that of patients participating in previous studies. (11,13,14) When comparing the scores of each CRQ domain obtained for the Brazilian patients with those obtained for patients from other countries in which the CRQ was validated, (13,14) we observed that the scores found for the fatigue, emotional function and mastery domains in the present study (4.5 ± 1.2; 4.8 ± 1.0; and 5.1 ± 1.3, respectively) were similar to those found for the Spanish-language version (4.47 ± 1.20; 4.80 ± 1.26; and 5.0 ± 1.5, respectively) and those found for the German-language version, with the exception of the mastery domain (4.2 ± 1.2, 4.4 ± 1.0 and 4.4 ± 1.2, respectively). However, for the dyspnea domain, the score obtained for the Brazilian population was considerably higher (4.6 ± 1.3) than that obtained for the Spanish population (3.15 ± 1.00) and for the Germanspeaking population (3.17 ± 0.66), indicating a better quality of life for this domain.…”
Section: Resultsmentioning
confidence: 99%
“…The CRQ has been translated and validated for use in the Netherlands, (12) in Spain (13) and in three German-speaking countries (Switzerland, Germany and Austria). (14) It has proven to be useful in a variety of interventions in COPD, including pharmacological interventions (15) and rehabilitation. (14,16) In addition, among the instruments that specifically assess the quality of life of patients with COPD, the CRQ has proven to be superior to the SGRQ because it is more responsive to interventions, such as pulmonary rehabilitation programs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As measures of the effects of respiratory rehabilitation, the selfadministered standardised German Chronic Respiratory Disease Questionnaire (CRQ) [15,16] and 6-min walking distance, as well as the short-time maximum exercise capacity (steep ramp test) and maximum exercise capacity (incremental exercise test), were used. The measurement of these outcomes has been described in detail previously [13].…”
Section: Discussionmentioning
confidence: 99%
“…Die Daten− banken der American Thoracic Society (www.atsqol.org) oder die ¹Patient−Reported Outcome and Quality of Life Instruments" (www.proqolid.org) listen 8 englischsprachige Verfahren zur Er− fassung der krankheitsspezifischen Lebensqualität bei COPD−Pa− tienten auf. Allerdings dominieren ± auch im deutschsprachigen Raum ± vor allem 2 multidimensionale Verfahren die For− schung: der Chronic Respiratory Questionnaire (CRQ) [7,8] und der St. George Respiratory Questionnaire (SGRQ) [9,10]. Beide Fragebogen zeichnen sich durch vergleichbare, zufriedenstellen− de psychometrische Kennwerte in Bezug auf Reliabilität und Va− lidität aus [11,12], benötigen jedoch aufgrund ihrer Länge zwi− schen 15 und 20 Minuten Durchführungszeit und konnten sich in der alltäglichen pneumologischen Praxis nicht durchsetzen.…”
unclassified